Numerical Investigation of Photonic Crystal Fiber-Based Biosensor for Pathogens Detection in Water - Emranul Haque; Abdullah Al Noman; Feroz Ahmed (IEEE Access, 2022)
In this paper, a Photonic Crystal Fiber (PCF) based Surface Plasmon Resonance (SPR) biosensor for the detection of four bacteria such as Vibrio Cholera, Escherichia Coli (E. coli), Bacillus Anthracis, and Enterococcus Faecalis is proposed and evaluated numerically using finite element method (FEM)-based simulation tool. The proposed sensor exhibits excellent performance characteristics and has the configuration of identifying analyte samples externally. The sensor is designed with a basic square lattice of PCF, covered with a thin chemically stable gold layer. The proposed sensor can detect these four bacteria from pure water and has the highest wavelength sensitivity of 5161 nm/RIU for Enterococcus Faecalis. Other critical parameters such as Signal to Noise Ratio, Detection Limit, Sensor Length, Quality Factor, and Detection Accuracy are also calculated and presented for the proposed PCF biosensor.